Urbanization Primer. Project Assessment, Site Analysis, Design Criteria for Site and Services or Similar Dulling Environments in Developing Areas, with a Documentary Collection of Photographs on Urbanization. - Caminos, H.; Goethert, R. (My University, 1978)
Dies ist ein Nachschlagewerk und Handbuch zur Formulierung von Strategien, Projektvorschlägen etc. von Urbanisierungsprojekten in der Dritten Welt.
Keywords: Standortanalyse; Projektbeschreibung; Entwicklungsland; Urbanisierung; Stadtgestaltung; Stadtentwicklung